2022
DOI: 10.3390/ani12091151
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Neutrophil Extracellular Traps Formation by Cl-Amidine Alleviates Lipopolysaccharide-Induced Endometritis and Uterine Tissue Damage

Abstract: Endometritis is a common disease that affects the production in dairy cows and leads to severe losses in the dairy industry. Neutrophil extracellular traps (NETs) formation promotes pathogenic invasions of the lumen of the tissue, leading to inflammatory diseases such as mastitis, pancreatitis, and septic infection. However, research that could show the relationship between NETs and endometritis isscarce. Cl-amidine has been shown to ameliorate the disease squealing and clinical manifestation in various diseas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 71 publications
0
4
0
Order By: Relevance
“…Control Injection of 1 mg/kg saline into the uterus Model Injection of 1 mg/kg of 1 mg/mL LPS into the uterus [20] Metronidazole Injection of 1 mg/kg of 1 mg/mL LPS into the uterus, and intraperitoneal injection of 135 mg/kg/day metronidazole for 5 consecutive days [21]…”
Section: Group (N = 5) Treatmentmentioning
confidence: 99%
See 1 more Smart Citation
“…Control Injection of 1 mg/kg saline into the uterus Model Injection of 1 mg/kg of 1 mg/mL LPS into the uterus [20] Metronidazole Injection of 1 mg/kg of 1 mg/mL LPS into the uterus, and intraperitoneal injection of 135 mg/kg/day metronidazole for 5 consecutive days [21]…”
Section: Group (N = 5) Treatmentmentioning
confidence: 99%
“…Grouping of rats and the exact treatments given to every group are presented in Table 1 (Ref. [20][21][22]). After treatments, the remaining total 25 rats (5 rats per group) were euthanized by cervical dislocation after being anesthetized, and uterus was extracted from each rat, fixed for 24 h in 4% paraformaldehyde, dehydrated and embedded in paraffin, and cut into 8-µm-thick sections.…”
Section: Establishment Of Endometritis Rat Modelmentioning
confidence: 99%
“…Inhibitor of PAD4 Renal IRI Renal IRI mouse [130] Lung injury SAH mouse [131] Hepatocellular carcinoma Hepa1-6 bearing mouse [132] Breast cancer 4T1-bearing mice [28,129] Cl-amidine Inhibitor of PAD4 Mastitis LPS-induced mouse mastitis [133] Endometritis LPS-induced rat endometritis [134] BMS-P5 Inhibitor of PAD4 NETs is crucial for tissue homeostasis and avoiding the presentation of self-antigens [123]. Evidence showed that inhibiting NET formation by the treatment of Dnase I significantly protected hepatocytes and reduced inflammation after liver ischemia/reperfusion (I/R) injury [121], lessened lung injury, and improved survival both in mouse models and in humans with ARDS from pneumonia or sepsis [122].…”
Section: Gsk484mentioning
confidence: 99%
“…It was reported that Cl-amidine could also weaken the inflammatory response of LPS-induced endometritis in rats by decreasing the formation of NETs [134]. BMS-P5 is a novel PAD4-specific inhibitor.…”
Section: Gsk484mentioning
confidence: 99%